An Early Detection of Decline in Rotavirus Cases during the 2013/2014 Season in Japan as Revealed by Time-series Analysis of National Surveillance Data - Hashizume, Masahiro (Trop Med Health, 2015)
Rotavirus is a leading cause of severe acute gastroenteritis in children worldwide, and globally licensed vaccines are available. To expedite the introduction of rotavirus vaccines in the national immunisation programme, a simple, ecological method to monitor changes in the burden of rotavirus disease may be of great help. Here, we report an application of a time-series analysis on a publicly-available dataset in Japan on the weekly number of laboratory-confirmed rotavirus-positive samples over the last 5 year period between the 36th week of 2009 and the 35th week of 2014 during which rotavirus vaccines became marketed in Japan and presumed to reach an uptake rate of at least 39% as a national average. Compared with the expected number of rotavirus detection based on the preceding four rotavirus seasons, the number of rotavirus detection during the 2013–2014 season was 42.9% (95% CI: 38.6, 47.8). This suggests that the use of rotavirus vaccine had a positive impact on reducing the burden of rotavirus diarrhoea in Japan. This method, because of its simplicity and little cost, should be applicable to early detection of the impact of rotavirus vaccine even in resource-poor countries where the World Health Organization funded and implemented the sentinel surveillance programmes of laboratory-confirmed rotavirus cases.